2018
DOI: 10.1080/00103624.2018.1435679
|View full text |Cite
|
Sign up to set email alerts
|

Common Bean Productivity Following Diverse Boron Applications on Soil

Abstract: Aspects related to micronutrients management are still poorly studied and need to be clarified to guarantee sustainable production. In this way, the study aimed to evaluate boron (B) fertilization effects on nutrition and production of common beans. The parameters measured were relative chlorophyll index, dry mass, boron transport, utilization and absorption efficiencies, B content, and B accumulation in plant tissues. The study showed that the dry mass production was negatively affected by B application, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
2
Order By: Relevance
“…A similar trend in pear trees was reported by Wang et al (2011), who obtained a significant decrease of 37.60% as they increased the dose of B applied hydroponically, taking as control the dose of 10 ppm and increasing it up to 500 ppm. These results can be explained by the findings of Flores et al (2018), which indicate that an increase in B fertilization has no effect on nitrogen metabolism, which is strongly related to chlorophyll content. Figure 6.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 84%
“…A similar trend in pear trees was reported by Wang et al (2011), who obtained a significant decrease of 37.60% as they increased the dose of B applied hydroponically, taking as control the dose of 10 ppm and increasing it up to 500 ppm. These results can be explained by the findings of Flores et al (2018), which indicate that an increase in B fertilization has no effect on nitrogen metabolism, which is strongly related to chlorophyll content. Figure 6.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 84%
“…The variations in the effects for the chlorophyll content in the plants of soil fertilization treatments with varied doses of micronutrient (adopting B as reference) revealed that the supply of up to 4.0 kg ha -1 of the micronutrient did not affect the chlorophyll index at 28 and 46 days after emergence (Flores et al 2018a), the fertilization with 4.39 kg ha -1 promoted a higher chlorophyll index at 40 days after germination (Flores et al 2017), while doses up 6.0 kg ha -1 reduced pigment rates in common bean leaves (Flores et al 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Contudo as plantas deficientes em boro apresentam aumento na atividade da RNAase, que é uma enzima responsável por hidrolisar o RNA e possuem menor síntese de uracila a partir do ácido orótico. Visto que o boro participa do metabolismo do RNA e está relacionado a síntese do uracil, que é considerado como um dos componentes do RNA (FLORES et al, 2018b).…”
Section: Deficiência Por Borounclassified
“…Quando utilizado em concentrações elevadas o boro pode inibir o crescimento das plantas (ALI et al, 2013). Flores et al (2018b), verificaram que a cultivar de feijão Esplendor demonstrou elevada capacidade de absorção de boro, podendo atingir até 175 mg kg-¹. Porém os níveis elevados de absorção do elemento, ocasionaram fitotoxicidade e reduziram a produção da matéria seca em torno de 30%.…”
Section: Toxicidade Por Borounclassified